PROFESSIONALIZING EDUCATION, EDUCATORS, AND EDUCATIONAL INSTITUTIONS IN MANIFESTING “INDONESIA GOLDEN” - Ujang Permana; Darmasta Maulana; Sofyan Sauri; Ujang Cepi Barlian (International Journal Labs, 2022)
The problem of professionalism always has implications for the selling value of an educational institution. The achievement and prestige of institutions become highly dependent on the quality of learning, facilities, and infrastructure, supporting facilities, teachers and students, as well as learning outcomes. This research aims to find out about the professionalization of education, educators, and educational institutions to meet Indonesia gold in MIS Nurul Siti Aisyah Ishak Delitua. The type of research used is qualitative descriptive. Based on this research, it can be concluded that the improvement of educational professionalism can be achieved through the collectivity of the education system involving various aspects such as curriculum, education policy, materials, strategies, learning approaches and methods, facilities, facilities, and infrastructure, educators and education, managerial processes carried out professionally, learning processes, applications of information and communication technology, especially in the learning process in the classes, appropriate evaluation and control and control of the quality of education. In addition, the level of professionalism of an educational institution can be seen from the weight of accreditation. The scope of accreditation includes: First, institutional accreditation is an assessment of vocational education institutions, while accredited include: a) Curriculum / PBM; b) Organization, administration, and management; c) Sarana infrastructure; d) Power; e) Naming; f) Students; g) Community participation, and h) The school culture or culture.